Calculative Experiment and Field Observations of Split Phase Galloping with Oscillation Damper - I. I. Serguey; P. I. Klimkovich; А. A. Vinogradov; J.-L. Lilienne (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2007)
The paper presents a numerical calculation method of split phase galloping of aerial power line which is based on equivalent wire model. Mathematical model of combined galloping damper dynamics is cited in the paper. Comparison of calculative and experimental parameters of single- and double– semi-wave galloping of KazSRIP experimental span for various initial glaciation angles. An efficiency evaluation of damping single- and double- semi-wave galloping by combined dampers is given in the paper. Reliability of this evaluation has been verified by experimental data.